2021
DOI: 10.3390/agronomy11020281
|View full text |Cite
|
Sign up to set email alerts
|

Field Screening of Wheat Advanced Lines for Salinity Tolerance

Abstract: Salinity in soil or irrigation water requires developing genetically salt-tolerant genotypes, especially in arid regions. Developing salt-tolerant and high-yielding wheat genotypes has become more urgent in particular with continuing global population growth and abrupt climate changes. The current study aimed at investigating the genetic variability of new breeding lines in three advanced generations F6–F8 under salinity stress. The evaluated advanced lines were derived through accurate pedigree selection unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 33 publications
4
29
0
Order By: Relevance
“…The genotypes; G-123, G-126, and G-2000 produced highest forage yield, crude protein, grain yield and its components as well as biological yield. Such differences were due to genetic variation in used genotypes and their interaction with environmental conditions [18,29]. These results are in accordance with those reported by Royo et al [49]; Kaur et al [52]; Sharma [32]; Hundal et al [33]; Choudhary and Chaplot [51]; Hajighasemi et al [44]; and Kandic et al [35].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The genotypes; G-123, G-126, and G-2000 produced highest forage yield, crude protein, grain yield and its components as well as biological yield. Such differences were due to genetic variation in used genotypes and their interaction with environmental conditions [18,29]. These results are in accordance with those reported by Royo et al [49]; Kaur et al [52]; Sharma [32]; Hundal et al [33]; Choudhary and Chaplot [51]; Hajighasemi et al [44]; and Kandic et al [35].…”
Section: Discussionsupporting
confidence: 89%
“…Wheat, barley, triticale, and oat are commonly cultivated for dual-purpose in the Mediterranean basin [12][13][14]. However, barley is advantaged by its tolerance to salinity and therefore producing higher biomass under salinity stress compared with other cereal crops [15][16][17][18]. In addition, it is characterized by rapid re-growing after grazing while maintaining similar yield levels to that of un-grazed ones [19].…”
Section: Introductionmentioning
confidence: 99%
“…The present study demonstrated that soil salinity (200 and 250 mM NaCl) caused a considerable reduction in plant productivity (Figures 1 and 2). This reduction is attributed to the influence of osmotic pressure produced by salinity worsening metabolic functions and to the reduction in energy requirements and cellular divisions [48][49][50]. Salinity adverse effects led to a reduction in leaf photosynthetic pigments, photosynthetic efficiency, stomatal closure, imbalance in ionic and gas exchange, toxic ion uptake and, subsequently, growth inhibition [3,51].…”
Section: Discussionmentioning
confidence: 99%
“…Sinai has saline water and soil, which affect the growth of different crops [ 37 ]. For instance, several Egyptian wheat genotypes were studied under salinity stress, and genetic divergence was detected by evaluating genotypes under the Sinai environment using molecular and biochemical indicators [ 38 , 39 ]. In our study, the phenotypic evaluation showed significant variations for salinity stress tolerance under saline conditions between various genotypes, indicating a potential of broad salinity tolerance within the global chickpea population.…”
Section: Discussionmentioning
confidence: 99%